Efetividade deliberativa no âmbito do conselho municipal dos direitos da criança e do adolescente de Goiânia - Tôrres, Renato Meneses (2018)
It is surprising to note that democracy emerges as a desirable universal value of humanity at the same time that it is singled out as a culprit for a generation. The disappointment with traditional representative institutions suggests the deepening of democracy and the search towards alternatives that require greater participation and involvement of society in public issues. Post-transition Brazil is a country that thrives with the experimentation of participatory projects: rights’ councils, participatory budgeting, ombudsman’s offices, popular legislative initiatives, controllerships, conferences, public hearings. In addition, upon the completion of thirty years of the promulgation of the Federal Constitution of 1988 (CF/88), a charter that includes important participation institutes – in particular, it provides for the creation of the councils of rights as joint participation spaces between State and society civil - it is natural to ask about the results obtained by these instances, that is, their effectiveness, considering the association between participation and public policies. From this perspective, this study aims to analyze and understand the Municipal Council of the Rights of the Child and the Adolescent (CMDCA) of Goiânia on two aspects: first, regarding the outcomes of the Council’s performance, that is, its capacity to influence, control and decide on public policy in the area of children and adolescents; second, with greater emphasis, focused on the process, that is, on the institutional design of the agency, on the interaction between the Directors and possible obstacles to its operation. Preliminarily, we raised the possibility that the nonconfluence around a participatory project on the part of the State apparatus would incur in the ineffectiveness of this agency. For this purpose, a documentary analysis was carried out, including municipal legislation, minutes, edicts and resolutions of the council, observation of deliberations and semi-structured interviews. Taking advantage of a large body of theoretical references, we analyzed the different degrees of institutionalization, democratization and representation in the deliberative practice of the council. After using this methodology of investigation of the minutes and documents we understood that, even though they have been present at a good level since its origin, the agency faces difficulties in constituting itself as a guiding entity of public policies. By restricting its field of action as a participatory instance to essentially bureaucratic guidelines the CMDCA Goiânia, although fulfilling the functions for which it was created and whose actions are fundamental to the execution of the child and adolescent care policy, relegates important attributions as formulator agent of the area’s policy by becoming a mere legitimator of the actions of the municipality. Nevertheless, beyond these observations and the discussion on effectiveness, the importance of the agency remains evident in terms of its pedagogical character, political formation, preparation for debate, the perennial exercise of tolerance and respect for the opinion of others, so rare nowadays, despite the adverse conditions imposed by the municipality.